When did the ancestor of true bugs become stinky? Disentangling the phylogenomics of Hemiptera–Heteroptera. (19th December 2017) - Wang, Yan‐Hui; Wu, Hao‐Yang; Rédei, Dávid; Xie, Qiang; Chen, Yan; Chen, Ping‐Ping; Dong, Zhuo‐Er; Dang, Kai; Damgaard, Jakob; Štys, Pavel; Wu, Yan‐Zhuo; Luo, Jiu‐Yang; et al.
Abstract: The phylogeny of true bugs (Hemiptera: Heteroptera), one of the most diverse insect groups in terms of morphology and ecology, has been the focus of attention for decades with respect to several deep nodes between the suborders of Hemiptera and the infraorders of Heteroptera. Here, we assembled a phylogenomic data set of 53 taxa and 3102 orthologous genes to investigate the phylogeny of Hemiptera–Heteroptera, and both concatenation and coalescent methods were used. A binode‐control approach for data filtering was introduced to reduce the incongruence between different genes, which can improve the performance of phylogenetic reconstruction. Both hypotheses (Coleorrhyncha + Heteroptera) and (Coleorrhyncha + Auchenorrhyncha) received support from various analyses, in which the former is more consistent with the morphological evidence. Based on a divergence time estimation performed on genes with a strong phylogenetic signal, the origin of true bugs was dated to 290–268 Ma in the Permian, the time in Earth's history with the highest concentration of atmospheric oxygen. During this time interval, at least 1007 apomorphic amino acids were retained in the common ancestor of the extant true bugs. These molecular apomorphies are located in 553 orthologous genes, which suggests the common ancestor of the extant true bugs may have experienced large‐scale evolution at the genome level.